The Profile of Karang Taruna Nagari Taratak Baru Koto Laweh Solok District - Salki Dihami, Altel; Irmawita, Irmawita (Universitas Negeri Padang, 2023)
This research is motivated by the profile and work program of the Nagari Taratak Baru Koto Laweh youth organization. The purpose of this research is to describe the profile of the youth group of Nagari Taratak Baru Koto Laweh, Solok Regency and also to describe the work program of the youth organization in improving the social welfare of the community in Nagari Taratak Baru Koto Laweh, Solok Regency.This study used qualitative research methods. The qualitative research method aims to describe what it is, thoroughly analyze the data obtained in the hope of knowing how the youth program in Nagari Taratak Baru Koto Laweh is. The data sources in this study were the chairman of the Nagari Taratak Baru Koto Laweh youth organization, Solok Regency and members of the Karang Taruna as well as documentation. Data collection techniques were carried out by observation, interview and documentation methods. For data validity using data source triangulation.The results of this study indicate that the profile of the new Taratak Nagari Nagari Youth Organization can improve the social welfare of the community with useful activities and work programs at the new Taratak Nagari Youth Organization, Koto Laweh.